A Phonological Analysis of the Kedah Malay Kunluang Sub-dialect in Wayang Kulit Seri Asun: (Analisis Fonologi Subdialek Melayu Kedah Kunluang dalam Wayang Kulit Seri Asun) (Jurnal Bahasa, 2019)
This study discusses and analyses the phonology of the Kedah Malay Kunluang sub-dialect (SMKK) in the Wayang Kulit Seri Asun. The Kedah Malay Kunluang sub-dialect (SMKK) is one of the sub-dialects of northern Kedah, and is spoken from northeastern Jitra to the Thailand-Malaysia border, according to Asmah (1988). This study aims (1) to complement the study of subdialectal variations of areas, districts and sub-districts and (2) to study if there is any element of influence from the Kedah Siamese dialect in SMKK. The data analysis was performed based on the phonological processes according to the Generative Phonological Theory of Chomsky and Halle (1968). Analysis of the data is described from input (Underlying Structure) to the output (Surface Structure) to provide a representation of the actual pronunciation of SMKK native speakers. The findings of this study show that phonological processes that occur in SMKK consists of diphthongization, vowel lengthening, vowel lowering, consonant replacement, consonant changes, nasal assimilation, consonant deletion, glottalization, vowel nasalization, and insertion. This shows that SMKK phonological processes are in unity with the Kedah Standard dialect and have not received any influence from the Kedah Siam dialect, even though SMKK is spoken in the Kubang Pasu district near Padang Terap, Kuala Nerang and others that have received obvious influences from the Kedah Siam dialect.Keywords: Phonology, phonological processes, Malay Kedah dialect, the Malay Kedah Kunluang sub-dialect, Wayang Kulit Seri Asun